Features, problems and prospects of development of the national transport system of the Republic of Kazakhstan - Allahverdieva, L.M.; Кurmanalina А.А.; Таsmaganbetova S.Zh. (BUKETOV BUSINESS REVIEW, 2019)
Currently, much attention is paid to the implementation of transport and innovation projects in the Republic of Kazakhstan and the world, such transport and logistics projects as «Silk road Economic belt», «Western Europe — Western China», block train «Silk Wind», FEZ «Khorgos-Eastern gate», Kazakhstan-Chinese international center for cross-border cooperation, international transportation «Rail Air». In the article the existing problems, peculiarities of organization and development of the national transport system of Kazakhstan are analyzed. At the same time, the added value of GDP of Kazakhstan in the National transport system of the Republic of Kazakhstan, transport and cargo turnover, indicators of labor intensity and return of wages of the transport industry of the Republic of Kazakhstan, the coefficient of depreciation of fixed assets of the transport industry, indicators of stock lighting and labor productivity of the transport industry, capital productivity and resource intensity of the transport industry, the efficiency of the transport industry in the Republic of Kazakhstan are reflected. The analysis and evaluation of passenger traffic and passenger transportation, freight and cargo transportation in the Republic of Kazakhstan is made. The socio-economic prerequisites, directions of the choice of the international transport strategy of Kazakhstan with neighboring and partner countries are considered.